The Impact of Frailty on the Risk of Conversion from Mild Cognitive Impairment to Alzheimer’s Disease: Evidences from a 5-Year Observational Study - Trebbastoni, Alessandro; Canevelli, Marco; D’Antonio, Fabrizia; Imbriano, Letizia; Podda, Livia; Rendace, Lidia; Campanelli, Alessandra; Celano, Valentina; Bruno, Giuseppe; de Lena, Carlo (Frontiers in Medicine, 2017)
The frailty construct has increasingly been adopted in the field of cognitive disorders. The aim of the present study was to measure frailty in a cohort of individuals with mild cognitive impairment (MCI) and to explore whether frailty measures may consent to predict the risk of conversion to dementia. We retrospectively reviewed the clinical charts of outpatients with amnesic MCI (aMCI) consecutively recruited at our Department, and followed-up for 5 years. Individual frailty status was measured by means of a frailty index (FI) consisting of 39 deficits (including signs, symptoms, diagnoses, and disabilities). Univariate analyses were used to compare the socio-demographic and clinical characteristics between subjects converting or not converting to probable Alzheimer’s disease (AD) dementia over the follow-up. Risk for conversion to AD dementia was assessed using Cox regression models. Ninety-one subjects with aMCI (mean age 72.7, SD 7.1 years; women 49.5%) were consecutively recruited over a period of 12 months. Low levels of frailty were documented in the sample (mean FI score 10.0, SD 5.3). A statistically significant correlation between age and FI was observed. Overall, 58 participants converted to AD dementia over time. The Cox regression analysis showed that age (HR: 1.04, 95% CI: 1.00–1.08), male sex (HR: 0.52, 95% CI: 0.30–0.91), Mini–Mental State Examination score (HR: 0.85, 95% CI: 0.77–0.94), and FI (HR: 1.11, 95% CI: 1.05–1.18) were all significantly associated with the probability of MCI conversion. Individual’s frailty status may increase the risk of conversion from a condition of MCI to overt AD dementia. The adoption of constructs comprehensively reflecting the biological decline of the aging subject may add useful estimates and information in the clinical approach to cognitive disorders.